Whole genome sequencing of Malaysian colorectal cancer patients reveals specific druggable somatic mutations - Mohd Yunos, Ryia Illani; Ab Mutalib, Nurul-Syakima; Khoo, Jia-shiun; Saidin, Sazuita; Ishak, Muhiddin; Syafruddin, Saiful Effendi; Tieng, Francis Yew Fu; Md Yusof, Najwa Farhah; Abd Razak, Mohd Ridhwan; Mahamad Nadzir, Norshahidah; Abu, Nadiah; Rose, Isa Md; et al. (Frontiers in Molecular Biosciences, 2023)
The incidences of colorectal cancer (CRC) are continuously increasing in some areas of the world, including Malaysia. In this study, we aimed to characterize the landscape of somatic mutations using the whole-genome sequencing approach and identify druggable somatic mutations specific to Malaysian patients. Whole-genome sequencing was performed on the genomic DNA obtained from 50 Malaysian CRC patients’ tissues. We discovered the top significantly mutated genes were APC, TP53, KRAS, TCF7L2 and ACVR2A. Four novel, non-synonymous variants were identified in three genes, which were KDM4E, MUC16 and POTED. At least one druggable somatic alteration was identified in 88% of our patients. Among them were two frameshift mutations in RNF43 (G156fs and P192fs) predicted to have responsive effects against the Wnt pathway inhibitor. We found that the exogenous expression of this RNF43 mutation in CRC cells resulted in increased cell proliferation and sensitivity against LGK974 drug treatment and G1 cell cycle arrest. In conclusion, this study uncovered our local CRC patients’ genomic landscape and druggable alterations. It also highlighted the role of specific RNF43 frameshift mutations, which unveil the potential of an alternative treatment targeting the Wnt/β-Catenin signalling pathway and could be beneficial, especially to Malaysian CRC patients.